Mediasi Kepuasan Pelanggan Dalam Pengaruh Preferensi Pelanggan Dan Penjualan Adaptif Terhadap Kepercayaan Pelanggan Perumahan Klaster Di Kabupaten Jember - R. Alamsyah Sutantio (Fakultas Ekonomi dan Bisnis, 2018)
R. AlamsyahSutantio, SE, MSi, Doctoral Program of Management Science, Marketing Management Interests Faculty of Economics and Business, University of Jember, 2018. The mediation of customer satisfaction in the effect of customer preference and adaptive sales on cluster housing customer trust in Jember, Promoter: Prof. Dr. R. Andi Sularso, MSM; Co-Promoter 1: Dr. Bambang Irawan, MSi; Co-Promoter 2: Dr. Mohammad Dimyati, SE, MSi. The growth of population in Jember Regency is an opportunity for property business, supported by high purchasing power of many cluster type housing offered by the developers. Cluster-type house isa one-door access housing that depicts modern lifestyle, social identity, style, trend supported by purchasing power and various facilities and infrastructure facilities offered by developers. The number of developers and cluster type houses offered cause competition among developers. Customer satisfaction impacts customer trust on developers. Severalfactors which can affect customer satisfaction are customer preference and adaptive sales, customer satisfaction as a mediation of customer trust on the developer. The data collection method in this study issurvey. Populations and samples are customers who have purchased a cluster house. Sampling method usesproportional random sampling with questionnaire and the data analysis uses Generalized Structured Component Analysis (GeSCA). The result of this study indicates that adaptive sales have a higher role compared to customer preference as mediation on cluster housing customer trust. This research finds a model of how to build customer trust on the developer through the enhancement of the adaptive sales capabilities of the salesperson.
Reupload file repository 6 april 2026_kur/feren
Keywords: customer preference; adaptive selling